2012
DOI: 10.1371/journal.pone.0038201
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Brain Function and Changes with Intervention in Children with Poor Spelling and Reading Abilities

Abstract: Previous fMRI studies in English-speaking samples suggested that specific interventions may alter brain function in language-relevant networks in children with reading and spelling difficulties, but this research strongly focused on reading impaired individuals. Only few studies so far investigated characteristics of brain activation associated with poor spelling ability and whether a specific spelling intervention may also be associated with distinct changes in brain activity patterns. We here investigated su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…Prior to treatment, L posterior cingulate activation was negatively correlated in whole-brain multivariate patterns predicting responsiveness to intervention [108]. At post-intervention, poor spellers/readers showed increased activation in R posterior cingulate cortex when compared with a no-treatment group [101]. At treatment follow-up, children with RD showed greater activation than controls in R posterior cingulate [69].…”
Section: Resultsmentioning
confidence: 91%
“…Prior to treatment, L posterior cingulate activation was negatively correlated in whole-brain multivariate patterns predicting responsiveness to intervention [108]. At post-intervention, poor spellers/readers showed increased activation in R posterior cingulate cortex when compared with a no-treatment group [101]. At treatment follow-up, children with RD showed greater activation than controls in R posterior cingulate [69].…”
Section: Resultsmentioning
confidence: 91%
“…At least three fMRI studies of children or adults with dyslexia have found that various interventions can lead to both improved reading and increased activation in the hippocampus and other MTL structures (as well as other brain regions) in phonological processing and pseudoword reading tasks, suggesting an increased dependence on these structures (Eden et al, 2004; Gebauer et al, 2012; Temple et al, 2003). It has been argued that this pattern may be due to compensation by hippocampal-based memory (Temple et al, 2003) – though for this and other findings, it is important to keep in mind that inference of function from a given activation pattern is often uncertain (for a discussion of the issue of inference in neuroimaging studies, see Poldrack, 2006).…”
Section: A Compensatory Role For Declarative Memory?mentioning
confidence: 99%
“…Functional and structural MRI evidence: Behavioral interventions lead to increased hippocampal activation and volumes (Eden et al, 2004; Gebauer et al, 2012; Krafnick et al, 2011; Temple et al, 2003)…”
Section: Figurementioning
confidence: 99%
“…Dynamic and influential learning involving WM occurs throughout life, but is especially critical during development, as organisms establish the infrastructure and patterns of circuitry in the brain. Spelling impairment is associated with DTI differences in WM integrity [104], and five weeks of remediation improved spelling and reading comprehension versus controls [105]. This increase in WM FA in language relevant networks highlights the importance of WM plasticity in cognitive learning.…”
Section: Environmentally Influenced Changes In Myelin Structure and Fmentioning
confidence: 99%